การพัฒนาแบบประเมินรูปแบบการรับความรู้สึก สาหรับเด็ก อายุ 3-12 ปี - นัชชา ชัยคาหล้า (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to develop of Sensory Patterns Assessment for 3-12 Year Children and to examine psychometric properties of the developed assessment including content validity, construct validity, internal consistency and intra-rater reliability. The sample were the students who were studying in early childhood program and grade 1-6 in Chiangmai primary education service area Office 1. The multi-stage sampling was used to select 408 participants. An instrument was Sensory Patterns Assessment for 3-12 Years Children. Teachers were informants who recorded the frequency of students’ behavior in their classes expressed into 6 categories: visual, auditory, olfactory and taste, vestibular, tactile, proprioceptive and 4 patterns, Low Registration, Sensory Seeking Sensory Sensitivity, and Sensory Avoiding. Results revealed that the index of congruence (IOC) was between 0.8-1.0. The Cronbach's alpha is equal to 0.97. The intra-rater reliability (ICC) was 0.96. The results of construct validity using factor analysis revealed that Sensory Patterns Assessment consists of 106 questions. The Cronbach's alpha is equal to 0.97. The intra-rater reliability (ICC) was 0.92. This indicates that the tool can be evaluated sensory patterns for 3-12 Year Children.